2020
DOI: 10.21203/rs.3.rs-26902/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of MTHFR C677T polymorphism with severity and localization of chronic atrophic gastritis patients without Helicobacter pylori infection : a case control study

Abstract: Abstract Background: Previous reports indicate that the methylenetetrahydrofolate reductase (MTHFR) 677C>T polymorphism plays a role in gastric cancer. However, whether it influences the development and progression of atrophic gastritis remains unclear. We aimed to determine the possible association between the MTHFR 677C>T polymorphism and the severity of atrophic gastritis.Methods: A total 128 patients withou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our study confirmed that H.pylori infection was related to gender and age. 38 Our study also found that the blood pressure (BP) in patients with H.pylori infection were higher than those without H.pylori infection. It was suggested that H.pylori infection might be a risk factor for cardiovascular and cerebrovascular diseases, 43 , 44 although the BP was in the normal range.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Our study confirmed that H.pylori infection was related to gender and age. 38 Our study also found that the blood pressure (BP) in patients with H.pylori infection were higher than those without H.pylori infection. It was suggested that H.pylori infection might be a risk factor for cardiovascular and cerebrovascular diseases, 43 , 44 although the BP was in the normal range.…”
Section: Discussionsupporting
confidence: 61%
“…This is similar to a study that TT genotype increases moderate to severe atrophic gastritis and gastric mucosal intestinal metaplasia in Chinese Han population without H.pylori infection. 38 Although many studies have shown that MTHFR C677T polymorphism was associated with gastrointestinal cancer, the specific relationship was not clear. 18 , 38 , 39 We speculated that the specificity of MTFHR C677T polymorphism for gastrointestinal cancer during H.pylori infection might be related to the site of cancer origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation